Critical Review of Cross-Cutting Themes in Global Healthcare - Alsayari, Fatemah Ayeed Salmeen; Alsaiari, Salaha Saleh Bishr; Alzogly, Mohammed Ahmad Ali; alsaad, Abdulmajeed salem; Almothel, Mana Saud Mohd; Alkorbi, Dawlah Nasser Salem; Albalawi, Nuha Faleh; Alhumaidi, Mohammed; Alyami, Ali Hussain Ahmed; Alshammmry, Sultana Hussean (Journal of Ecohumanism, 2024)
Global health is a bracing complex of multidimensional and cross-cutting issues that define health care and policy worldwide and the models of health care administration. These themes are UHC, social conditions influencing health, technology, health workforce, and climate change. This paper aims to review and contrast these themes through High-Income Countries and Low-Income Countries to identify key emerging challenges and opportunities in global health. The publication also considers the need to combine efforts and work intelligently to solve these problems, focusing on the organization’s work on the international level to create conditions for achieving improved health for everyone. Finally, the authors present policy implications that may help promote fair and sustainable models for healthcare organizations internationally.